Superior EMI shielding effectiveness with enhanced electrical conductivity at low percolation threshold of flexible novel ethylene methyl acrylate/single‐walled carbon nanotube nanocomposites. Issue 6 (6th April 2022) - Sit, Subhashis; Chakraborty, Goutam; Das, Narayan Chandra
Abstract: The rising trend of electromagnetic pollution has motivated us to develop a novel electromagnetic interference shielding (EMI) material by adopting a facile, industry viable, and cost‐effective solution mixing strategy. Single‐walled carbon nanotubes (SWCNT) as conductive fillers is employed in a lightweight, highly flexible ethylene methyl acrylate (EMA) polymer to fabricate the superior electrically conductive and efficient EMI shielding material at a relatively lower percolation threshold limit compared to other carbonaceous fillers has been justified by their morphological characterization. The electrical conductive network formation is attained at just 1.96 wt% of SWCNT loading resulting in more than 20 dB of EMI shielding effectiveness (EMI SE) dominated by absorption mechanism to fulfill the industrial requirement along with excellent mechanical properties improvement, and the highest SE is 45 dB at 15 wt% of reinforcement facilitating their potential use in both industry and academia. Abstract : Fabrication of a novel single‐walled carbon nanotubes (SWCNT)/ethylene methyl acrylate (EMA) nanocomposite with very low percolation threshold and its excellent flexibility, improved mechanical properties and enhanced electrical conductivity.